(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Bacterial infections caused by biofilm forming organisms are of public health concern due to their propensity to contribute to persistent chronic diseases, chiefly because of their ability to resist antibiotics and host immune functions. Probiotics are considered useful therapeutic option in combating pathogenic biofilms. This study evaluates the anti-biofilm properties of potential probiotic Lactic Acid Bacteria (LAB) and fermented maize supernatant (Omidun) against selected biofilm-forming pathogens. Crystal violet biofilm assay was used to determine LAB and Omidun biofilm inhibition and dispersion in selected pathogens (Pseudomonas aeruginosa, Coagulase-negative staphylococci (CoNS), S. aureu and Enteroaggregative Escherichia coli) at different concentration (1%, 10%, 50%, 100%) of neutralized and non-neutralized cell free supernatant (CFS). Percentage biofilm inhibitions and dispersions were evaluated, and data were analysed with ANOVA. Omidun and LAB showed promising biofilm inhibitory and dispersive effect against the selected pathogens. L. plantarum showed the greatest biofilm inhibitory effect (P. aeruginosa: 7.85%, CoNS: 27.75%, S. aureus: 66.90%, EAEC: 39.73%) and dispersive effect (P. aeruginosa: 15.94%, CoNS: 23.27%, S. aureus: 24.90%, EAEC: 32.09%) against the selected pathogens while Omidun showed the least biofilm inhibitory and dispersive effect against the selected pathogens. There was no significance difference in the percentage of biofilm inhibition and dispersion produced under different concentrations, neutralized and non-neutralized state. Pseudomonas aeruginosa was the most resistant pathogen while Enteroaggregative Escherichia coli (EAEC) was the most susceptible. Inhibition and dispersion of biofilm can be mediated by LAB and Omidun, these effects appear to be independent of the produced organic acids